Towards A Resilient And Sustainable Future: Examining The Interplay Of Procurement 4.0, Process Optimization, And Environmental Uncertainty - Iqbal, Javed; Ali, Dr. Arfan (Migration Letters, 2024)
International agreements like the 2030 Agenda and scholarly research show that businesses keep doing what they’re doing; they need to put in extra effort to make the world more sustainable. To achieve this, businesses must implement sustainable practices by adopting cutting-edge technologies to optimize their processes. The emergence of new technologies and companies’ digital transformation towards these technologies is revolutionizing companies’ operational and administrative processes and creating innovative digital products and services. This study aims to identify how procurement 4.0 implementation and digital transformations are related and how digital transformation impacts the intention to optimize the procurement process in achieving organizational sustainability performance. The moderating can’t effect of environmental uncertainty is also investigated. We surveyed large-scale manufacturers in Pakistan and analyzed survey results using covariance-based structural equation modeling (SEM) through AMOS-24. The respondents of this study were 397 procurement professionals who had relevant knowledge about the understudied area. The findings of this empirical study[1] revealed the positive influence of procurement 4.0 implementation on procurement process optimization. Moreover, results confirmed the mediating role of procurement process optimization in enhancing organizational sustainability performance. Furthermore, results revealed that technological environment uncertainty significantly moderates the relationship between procurement 4.0 implementation and procurement process optimization. Originality: The concept of "procurement 4.0" has recently emerged and is not widely researched yet. Especially in the context of emerging economies, it is very novel. Hence, this study can contribute a lot to digitalization literature, particularly in the context of 4.0.